2006
DOI: 10.1002/ajpa.20393
|View full text |Cite
|
Sign up to set email alerts
|

Statistical basis for positive identification in forensic anthropology

Abstract: Forensic scientists are often expected to present the likelihood of DNA identifications in US courts based on comparative population data, yet forensic anthropologists tend not to quantify the strength of an osteological identification. Because forensic anthropologists are trained first and foremost as physical anthropologists, they emphasize estimation problems at the expense of evidentiary problems, but this approach must be reexamined. In this paper, the statistical bases for presenting osteological and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 36 publications
2
62
1
Order By: Relevance
“…Here we expand on victim identification, making the simplifying assumption that there is no commingling of remains so that we are solely attempting to make identifications. Rather than working directly with posterior probabilities as in the previous section, we will work with likelihood ratios and prior odds as this is much more common in the disaster victim and personal identification literature (Goodwin et al, 1999;Adams, 2003b;Brenner and Weir, 2003;Alonso et al, 2005;Christensen, 2005;Lin et al, 2006;Steadman et al, 2006;Prinz et al, 2007;Kaye, 2009;Budowle et al, 2011;Butler, 2011;Hartman et al, 2011;Abraham et al, 2012;Montelius and Lindblom, 2012;Jackson and Black, 2013). As mentioned above, likelihood ratios from DNA are typically reported as the inverse of the population frequency for the matched (between ante-mortem and post-mortem) genotype, although this is only possible when a "direct reference" ante-mortem sample is available (so that the numerator is equal to 1.0).…”
Section: Identification In a "Closed Population" Mass Disastermentioning
confidence: 99%
See 2 more Smart Citations
“…Here we expand on victim identification, making the simplifying assumption that there is no commingling of remains so that we are solely attempting to make identifications. Rather than working directly with posterior probabilities as in the previous section, we will work with likelihood ratios and prior odds as this is much more common in the disaster victim and personal identification literature (Goodwin et al, 1999;Adams, 2003b;Brenner and Weir, 2003;Alonso et al, 2005;Christensen, 2005;Lin et al, 2006;Steadman et al, 2006;Prinz et al, 2007;Kaye, 2009;Budowle et al, 2011;Butler, 2011;Hartman et al, 2011;Abraham et al, 2012;Montelius and Lindblom, 2012;Jackson and Black, 2013). As mentioned above, likelihood ratios from DNA are typically reported as the inverse of the population frequency for the matched (between ante-mortem and post-mortem) genotype, although this is only possible when a "direct reference" ante-mortem sample is available (so that the numerator is equal to 1.0).…”
Section: Identification In a "Closed Population" Mass Disastermentioning
confidence: 99%
“…As an example of this more conservative approach, Steadman et al (2006) found that a particular pattern of dental pathology observed in a forensic case was never observed in a database sample of 29,152 individuals. They used a match probability of 1/29,153 in analyzing their case, on the presumption that had one additional case been sampled it would have yielded a match.…”
Section: Prior Probability Of a Correct Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In jury trials, experts are often advised to testify only to the likelihood ratio developed from the biological evidence. The jury then supplies its own prior odds based on the entire context (e.g., Steadman et al 2006).…”
mentioning
confidence: 99%
“…[23][24][25][26][27]. Considering that tooth structure is not remodeled during life, they offer a large amount of information for understanding the biological and social dynamics of past populations [3,14,28,29] and assist in the identification of missing persons through forensic anthropology procedures [30][31][32]. Modern Dental Anthropology is the result of systematic efforts carried out by research teams for decadesin order to strengthen the scientific nature of the discipline and tried to explain the enormous biological diversity of human populations.The vast amount of information generated byscholars such as A.Hrdlička, A. Dahlberg, S. Garn, R. Potter, G. Townsend, E.Harris, J. Irish, K. and T.Hanihara, J. Kieser, A. Goodman, K. Alt, S.Hillson,H.…”
mentioning
confidence: 99%